Ethno-veterinary Medicinal Preparations of Tribals from Shirpur Tahsil, Dhule District, Maharashtra, India - Patil, H. M.; Patil, S.J. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Ethnobotanical surveys can potentially bring out many different clues for the development of safe, effective and inexpensive indigenous remedies. Present study has been focused on tribals of Shirpur Tahsil Dhule district of Maharashtra, India. Field surveys of this area were carried out during 2010–2011 through several field visits and interviews. The aim of the present study was primarily to evaluate and inventory ethno-veterinary medicinal uses of the plants known to tribals and to encourage preservation of their culture, conservation and sustainable utilization of the plant wealth. After such survey made 21 plant species of angiosperms are found useful against the various common diseases occurring among the domestic animals of the tahsil. The plants used by the tribe are arranged alphabetically followed by family name, herbarium number, local name, parts used, method of preparation and mode of administration of the drug.